Juliusz Berger – actor of two stages - Napiontkowa, Maria (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article recalls the outstanding actor Juliusz Berger (1928-1999), who was oneof the few twentieth-century artists in Poland who played simultaneously in twodifferent languages – Polish and Yiddish. Raised in a completely assimilated intelligentsiahome in Łuck, deported deep into Soviet Union, he returned to the country,where he graduated from high school, law studies in Wrocław, and then joinedthe theater. He started his stage career at PTD in Wrocław under the supervision ofEdmund Wierciński and Wilam Horzyca. Here Ida Kamińska, who was alreadymanaging the Jewish Theater at that time, saw him and offered him the main rolein the play - her own adaptation of Eliza Orzeszkowa's novel Meir Ezofowicz, whichrequired him to master the Yiddish language, which he did not know.I present Berger's artistic profile on the example of his two most famousroles: Meir Ezofowicz from 1953 at the Jewish Theater and Tewi (Fiddler on theRoof, 1984) at the Musical Theater in Gdynia. The context for them is Brecht'sSchweizerkez [Schweizerkas] in Mutter Courage und ihre kinders (1957) and Cadykin An-ski's The Dybbuk (1991).